Mobile, Community‐Based Buprenorphine Treatment for Veterans Experiencing Homelessness With Opioid Use Disorder: A Pilot, Feasibility Study. Issue 6 (4th May 2020) - Iheanacho, Theddeus; Payne, Kevin; Tsai, Jack
Abstract : Background and Objectives: Adults experiencing homelessness with opioid use disorder (OUD) utilize buprenorphine (BUP), a first‐line medication for OUD, at very low rates. Innovative and tailored approaches are needed to reduce barriers to treatment and increase utilization of BUP in this population. This study describes a pilot Mobile Community‐based Access Team (M‐CAT) that used mobile technology and FaceTime in addition to existing community‐based case management programs to provide BUP treatment for veterans with OUD experiencing homelessness who had difficulties engaging in the regular BUP clinic. Methods: We conducted a retrospective chart review of veterans enrolled in M‐CAT or the usual BUP clinic between January 2015 and December 2017 (N = 36). We abstracted demographic, medical, substance use, prescription, health care utilization, and drug use data from medical records. Results: Twelve veterans were enrolled in M‐CAT and 24 were enrolled in BUP clinic. Mean retention in treatment was 19.2 months (standard deviation [SD] = 10.2) in M‐CAT and 36 months (SD = 27.6) in BUP clinic. At the endpoint, 66.7% (n = 8) in M‐CAT and 100% (n = 24) in BUP clinic remained on BUP. Discussion and Conclusion: M‐CAT is an innovative and tailored pilot project that successfully integrated specific OUD medication treatment into existing case management programs for veterans experiencing homelessness using mobile technology and Facetime. M‐CAT can potentially increase utilization of BUP for OUD among high‐risk population of veterans experiencing homelessness who are otherwise not engaged in treatment. Scientific Significance: Integrating telemedicine, BUP treatment, and community‐based case management to treat OUD among veterans experiencing homelessness is feasible with high treatment retention. (Am J Addict 2020;29:485–491)